Identification Of Damage To The Sirimau Protected Forest On Ambon Island - Fransina S Latumahina; Gun Mardiatmoko; Susilawati Susilawati (Tropical Small Island Agriculture Management, 2025)
The research was carried out in the Sirimau Protected Forest area of ​​Ambon Island in June – October 2024, several forms of damage in the protected forest are Konk, Cancer, Damage to leaf shoots or shoots, Broken or dead branches, Open Wounds, Termite Attacks, Liana, Brum, Moss, Broken Rod, Leaves Discoloration. The damage to the Sirimau Protected Forest has caused serious ecological impacts, especially the decline in the forest's ability as a primary water catchment and absorption area for Ambon City. This has implications for increasing the risk of hydrometeorological disasters, such as flash floods and landslides in downstream areas, and threatens the sustainability of clean water supplies for residents.